How Can Web Lessons Be Taught to Reduce Screen Fatigue, Motivational, and Concentration Problems in Different Disciplines? - Lepp, Marina; Luik, Piret; Tark, Triin Mirjam (Frontiers in Sociology, 2022)
When conducting web lessons after transitioning to online learning due to the coronavirus, lecturers can base their work on experiences gained during the emergency situation and instructions prepared by the teaching support staff. However, students' perception of engagement strategies, screen fatigue, difficulties motivating themselves and problems with concentrating on web lessons should be also taken into account. The goal of this research is to find out how students rate the importance of engagement strategies in web lessons and how the ratings differ between disciplines. Also, the study aims to investigate how concentration difficulties, students' motivational problems and screen fatigue are connected to student engagement strategies in web lessons. To achieve that goal, 430 students of the Faculty of Sciences and Technology and the Faculty of Social Sciences at the University of Tartu were surveyed and multivariate analyses of variance and correlational analyses were conducted. Regarding student engagement strategies, “Use of slides” was found to be the most important by students. This was followed by “Explaining what and why is being studied,” “Sharing the teacher's screen,” and “Recalling what has been learned before”. The least important engagement strategies are “Presentation of article-based tasks,” “Second teacher answers questions in a chat,” and “Use of breakout rooms”. Comparing the faculties there was a statistically significant difference in the ratings given to five engagement strategies. The results showed that concentration difficulties were not related to the ratings of student engagement strategies. However, some positive correlations were found between screen fatigue and motivational difficulties, and the ratings of student engagement strategies, indicating that proper engagement strategies for conducting web lessons can be a way of influencing more students and better course design can support different needs.